'Sialodiagnosing' HIV infection: A dissected review - Jagat Reddy R Chinnapolamada; Seethalakshmi Ashokan Chiranjeevi; Abhinaya Reddy Tupalli; Sridhar Reddy Erugula (Wolters Kluwer Medknow Publications, 2015)
Human immunodeficiency virus (HIV) antibody testing of saliva has been successfully used to detect HIV infection for surveillance and screening studies of various populations since 1986. Many articles have been published reporting the sensitivity and specificity of saliva tests to detect antibodies produced against HIV. In spite of the difference between the type of collection device and laboratory methodology, the results found the sensitivity and specificity to be very high (around 98-100% and 99.5-100%, respectively). However, there is no data available about the usage of oral fluid in screening the HIV patients in our country. This article attempts to review various studies that used saliva as a sample to diagnose HIV infection for its known advantages when compared to blood, which is the current golden standard in investigating this disease.